2000
DOI: 10.1073/pnas.97.1.320
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic LIM-only transcription factor Lmo2 regulates angiogenesis but not vasculogenesis in mice

Abstract: The LMO2 gene is activated by chromosomal translocations in human T cell acute leukemias, but in mouse embryogenesis, Lmo2 is essential for initiation of yolk sac and definitive hematopoiesis. The LMO2 protein comprises two LIM-zinc-finger-like protein interaction modules and functions by interaction with specific partners in DNA-binding transcription complexes. We have now investigated the role of Lmo2-associated transcription complexes in the formation of the vascular system by following the fate of Lmo2-nul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
166
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(176 citation statements)
references
References 39 publications
6
166
0
4
Order By: Relevance
“…In normal brains, Lmo2 is highly expressed in mouse vascular endothelium and is necessary for angiogenic remodeling of the existing capillary network into mature vasculature. 17,24 GBMs display an enriched vasculature phenotype, which is strongly correlated with tumor aggressiveness and poor patient outcomes. Our studies presented the first evidence that LMO2 modulates endothelial-like cell conversion of GSCs by directly regulating VE-cadherin transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…In normal brains, Lmo2 is highly expressed in mouse vascular endothelium and is necessary for angiogenic remodeling of the existing capillary network into mature vasculature. 17,24 GBMs display an enriched vasculature phenotype, which is strongly correlated with tumor aggressiveness and poor patient outcomes. Our studies presented the first evidence that LMO2 modulates endothelial-like cell conversion of GSCs by directly regulating VE-cadherin transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…The latter may be at the level of the pluripotent stem cell, at the level of the immediate multi-potential progeny or even perhaps before this, when mesoderm gives rise to these precursors ( Figure 2a). Furthermore, Lmo2 has a speci®c intraembryonic expression pattern, in endothelial cells and blood progenitor cells (Figure 3) (Delassus et al, 1999;Yamada et al, 2000). In mouse embryogenesis, haemangioblasts (putative common precursors of endothelium and blood cells) are thought to arise from unspeci®ed posterior mesoderm and thus the primary capillary network is made from these haemangioblasts.…”
Section: The Lmo2 Gene and Its Proteinmentioning
confidence: 99%
“…The more mature vascular system is made by the remodelling of primary capillary network, in the process called angiogenesis (Hanahan and Folkman, 1996). Again use of null mutations of the Lmo2 gene (Yamada et al, 2000), showed that formation of the primary capillary network does not require Lmo2 but re-modelling into mature vessels does. Thus Lmo2 is necessary for angiogenesis, but not for vasculogenesis.…”
Section: The Lmo2 Gene and Its Proteinmentioning
confidence: 99%
“…The lmo2 Ϫ/Ϫ embryonic stem (ES) cells are unable to contribute to any hematopoietic lineage in adult chimeras mice, showing its crucial role in the initiation of yolk sac and definitive hematopoiesis (Warren et al, 1994;Yamada et al, 1998). Although the lmo2 Ϫ/Ϫ ES cells generate capillary network normally at early developmental stages, chimeric mice carrying a high proportion of lmo2-null ES cells show marked disorganization of the vascular system after E10, indicating that lmo2 is a key player in angiogenesis (Yamada et al, 2000). In zebrafish, lmo2 was expressed in hemangioblasts (Thisse and Zon, 2002).…”
Section: Introductionmentioning
confidence: 99%